Political Communication in the Quranic Perspective: Ethical Principles for Contemporary Politics - Awla, Fikra; Rifai, Akhmad (State Islamic Institute of Bone, Indonesia, 2025)
This study examines political communication in the Qur'anic perspective with the aim of understanding ethical principles that can be applied in today's political life. The background of this study is the emergence of various problems in modern political practices, such as dishonesty, injustice, and lack of transparency. This research was conducted with a qualitative approach through a literature study, which examined Qur'anic verses and commentaries related to communication and leadership. The results show that the Qur'an teaches five main principles in political communication, namely honesty, justice, deliberation (shura), openness, and transparency. These principles are very relevant to the modern political context, as they can strengthen public trust and encourage more just and responsible leadership. This research contributes to providing an Islamic perspective as an ethical foundation for political communication. In conclusion, Qur'anic values remain relevant and important to be applied in building a political system that is more ethical, inclusive, and in favour of common welfare.